Global Debt Database : Methodology and Sources - Mbaye, Samba (IMF Working Papers; Working Paper ;, 2018)
This paper describes the compilation of the Global Debt Database (GDD), a cutting-edge dataset covering private and public debt for virtually the entire world (190 countries) dating back to the 1950s. The GDD is the result of a multiyear investigative process that started with the October 2016 Fiscal Monitor, which pioneered the expansion of private debt series to a global sample. It differs from existing datasets in three major ways. First, it takes a fundamentally new approach to compiling historical data. Where most debt datasets either provide long series with a narrow and changing definition of debt or comprehensive debt concepts over a short period, the GDD adopts a multidimensional approach by offering multiple debt series with different coverages, thus ensuring consistency across time. Second, it more than doubles the cross-sectional dimension of existing private debt datasets. Finally, the integrity of the data has been checked through bilateral consultations with officials and IMF country desks of all countries in the sample, setting a higher data quality standard.